ANALISIS IMPLEMENTASI KEBIJAKAN PENATAUSAHAAN DAN PERTANGGUNGJAWABAN KEUANGAN DAERAH PADA DINAS PENGELOLAAN KEUANGAN DAN ASSET DAERAH KOTA PALU - Mastura, Asharrini (Katalogis, 2013)
The purpose of this study was to identify and analyze policy implementation and administration of the Regional Financial Accountability Office of Financial Management and the Regional Asset Palu. The main theories used in this study are those of Edward III about four factors that influence policy implementation is communication, resources, disposition and the structure of the bureaucracy. This type of research uses descriptive survey techniques. The population numbered 189 people and drawn purposively sampled to obtain 40 respondents.The results indicate the implementation of policy at the Department of Revenue and Finance and Asset Management Palu District Administration policy and Financial Management Accountability consists of four indicators, namely communication, resources, disposition and the structure of the bureaucracy.Of the four sub indicators are still indicators that still need to be improved, namely sub-indicators of physical facilities, the implementor of policies and attitudes that lead policy makers on creating good results. While inhibiting factors or constraints that are more focused on the principle of disbursement mechanisms are not timely and orderly financial administration should be based on the Regulation of the Minister of Home Affairs Number 55 Year 2008. In addition, the quality of human resources is still low, facilities and infrastructure have not mamadai and lack of coordination between government Regional, Provincial and Central.